Bekämpning av vita flygare (Aleurotrachelus socialis) i kassava (Manihot esculenta) : fysikaliskt verkande insektsmedel : mortalitet och appliceringsteknik - Karlsson, Miriam Frida (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
The study was performed in southwest of Colombia in close collaboration with the interna-tional centre of tropical agriculture, CIAT and supervised from the university of Valle, Uni-valle, Cali, Colombia and from the Department of Landscape Management and Horticultural Technology, SLU, Alnarp, Sweden. The main purpose of this thesis was to evaluate six different non-conventional insecticides and their ability to control whitefly Aleurotrachelus socialis in cassava Manihot esculenta. The aim was also to evaluate the most appropriate application technique for these products which were: Agronim, Biomel, Bioneem, EcoSwing, Coco soap + chilli and L´Ecomix. The products are mainly based on vegetable oil, soap and plant extract and cause primarily a physical contact effect which affirm that it is fundamental to obtain a high coverage of the underside of the leaves, where A. socialis is present. Initial greenhouse trials were made, comparing four different stages of A. socialis; eggs, nymphs of first and second instars and adults. Mortality for each stage was measured for three concentrations of each product, by dipping leaves into the treatments. Additionally two spray equipments and four different nozzles were evaluated, measuring per-centage coverage of the lower surfaces of the leaves and calculating the dispersion in three levels in the foliage of cassava, in relation to the liquid amount used by the spray equipment and the nozzles. The differences in the coverage between the four nozzles were not signifi-cant; ~60% coverage was obtained in all three levels in the foliage. However, the flow rate (l/min) for the traditional nozzle was approximately three times higher than for Albuz ATR (size: lilac), Goizper 50/0,2/3 and TX SS 3, which also differ in droplet size. The different products were observed to reduce the number of A. socialis, especially in the nymphal stages. It was observed that oil in combination with soap probably could be used as a control method for A. socialis. Treatments with Biomel and Coco soap + Chilli had the high-est mortality for the four stages. Eventually a field trial was conducted with Biomel 5ml/l and Coco soap 7g/l + Chilli 10g/l simultaneously with two different nozzles. The differences in number of A. socialis between the different treatments, in the field trial, were not significant due to a low incursion in the field, in combination with an exceptionally high precipitation. The results show potential for reducing the amount of spray required by using nozzles produc-ing fine droplets and in the same time obtain a good coverage of the products to control A. socialis in cassava.